ANALISIS PEMBIAYAAN DALAM MENINGKATKAN KESEJAHTERAAN NASABAH PADA PNM MEKAAR SYARIAH CABANG GELUMBANG KABUPATEN MUARA ENIM - Ariska Mufaridhoh; Itsnaini Chusnul Khotimah; Darsi Ahmadan (Al-Iqtishad: Jurnal Ekonomi Syariah, 2024)
This research was conducted to determine the financing in improving customer welfare at PNM Mekaar Syariah Gelumbang Branch Muara Enim Regency. The purpose of this research is to understand the effectiveness of financing in helping customers improve their welfare at PNM Mekaar Syariah Gelumbang Branch Muara Enim Regency. This research uses a qualitative approach that is a type of field research or field research, because the information obtained and collected through direct observation in the field and through literature review. The types of data used in this study are primary data and secondary data, while the data sources in this study were obtained from direct observation and interviews with customers. Data analysis techniques are done by data reduction, data presentation and making conclusions. The results of this study indicate that customer income increased after taking financing at PNM Mekaar Syariah Gelumbang Branch, because PNM provides various services that help customers develop their businesses. The expenses of customers who take financing at PNM have been fulfilled, including food and non-food expensess. Financing from PNM Mekaar Syariah Gelumbang Branch has not been able to fully improve the level of family education, because one customer has not met the educational needs of one of her children.The customer???s family health level has been fulfilled through financing at PNM Mekaar Syariah Gelumbang Branch, this can be seen from a healthy lifestyle, regular chek-ups and buying health products. PNM has also improved the welfare of financing customers in housing conditions and facilities owned in the household, this is supported by the results of interviews with financing customers.